Direct‐to‐consumer genetic testing companies tell their customers to 'see a genetic counselor'. How do genetic counselors feel about direct‐to‐consumer genetic testing?. Issue 1 (24th July 2020) - Hsieh, Vicky; Braid, Tamara; Gordon, Erynn; Hercher, Laura
Abstract: Professional societies, the FDA, and many direct‐to‐consumer genetic testing (DTC‐GT) companies have highlighted the value of counseling from a medical professional with genetics expertise in order to enhance the value and minimize the risks associated with DTC‐GT. However, there is limited information available identifying genetic counselors' own views on DTC‐GT, their willingness to counsel consumers based on DTC‐GT results, and their experiences to date seeing DTC‐GT consumers in a clinical setting. We surveyed genetic counselors accessed through mailing lists associated with the National Society of Genetic Counselors (NSGC) and the American Board of Genetic Counseling (ABGC). Response rate was estimated to be 12.2% ( n  = 482). A majority of all respondents (56.4%, n  = 263) described themselves as feeling negatively or very negatively toward DTC‐GT; only 6.9% ( n  = 32) described themselves as feeling positively or very positively. While 90.9% of respondents ( n  = 398) believed that DTC‐GT would be improved with the involvement of genetic counselors, only 31.2% agreed or strongly agreed that they are comfortable providing counseling to DTC‐GT consumers ( n  = 142). Clinical counseling of DTC‐GT consumers is not routine but it is also not uncommon; 40.1% of all respondents ( n  = 189) have seen at least one consumer in clinic for the sole purpose of reviewing DTC‐GT results. The results of our study suggest that most respondents would be more accepting of DTC‐GT if genetic counseling was a part of the process, but the majority of counselors do not feel comfortable providing this service.